2009
DOI: 10.1345/aph.1m141
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Generic and Innovator Drugs: A Review of 12 Years of Bioequivalence Data from the United States Food and Drug Administration

Abstract: The criteria used to evaluate generic drug bioequivalence studies support the FDA's objective of approving generic drug formulations that are therapeutically equivalent to their innovator counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
226
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(245 citation statements)
references
References 40 publications
(38 reference statements)
14
226
1
4
Order By: Relevance
“…Relative magnitudes of clinical studies for generic medicines 64, biosimilar LY insulin glargine 32, 35, 37, 38, 41, 43 and new molecular entities 65. The sizes of the circles do not necessarily represent the relative sizes of the trials between categories.…”
Section: Differences Between Biosimilar and Generic Medicinesmentioning
confidence: 99%
“…Relative magnitudes of clinical studies for generic medicines 64, biosimilar LY insulin glargine 32, 35, 37, 38, 41, 43 and new molecular entities 65. The sizes of the circles do not necessarily represent the relative sizes of the trials between categories.…”
Section: Differences Between Biosimilar and Generic Medicinesmentioning
confidence: 99%
“…In a review of 12 years of bioequivalence data, the FDA found that the criteria used to evaluate generic drugs leads to the approval of generic versions that are bioequivalent to their brand counterparts within a narrow margin [6]. However, some drug products may have unique structural or functional attributes that necessitate product-specific approaches to therapeutic equivalence determinations.…”
Section: The Use Of Product-specific Therapeutic Equivalence Standardsmentioning
confidence: 99%
“…2 Generic drugs offer a powerful approach to cost savings for the patients. As a result patient compliance to the treatment increases.…”
mentioning
confidence: 99%
“…As a result patient compliance to the treatment increases. 1,2 In the year 2008 alone, generic drugs accounted for 69% of all prescriptions dispensed in the USA, yet only 16% of the cost in US dollar were spent on such prescriptions. 2 All prescriptions and over-the-counter generic drugs marketed in the USA must meet standards set by the US FDA.…”
mentioning
confidence: 99%
See 1 more Smart Citation